Profile of Colorectal Tumor in Gastroentero-Hepatology Center, Department of Internal Medicine, Dr Soetomo Hospital, Surabaya - Thamrin, Husin; Ilmiah, Khafidhotul; Tirthaningsih, Ni Wajan (Folia Medica Indonesiana, 2020)
Colorectal cancer has became burden in the world.The latest study shows that colorectal cancer is the third most common cancer in men and second most common cancer in women globally. There are difference characteristic of epidemiology in every countries. Moreover, there is no study that represents epidemiology of colorectal cancer in Indonesia yet, especially in East Java. The aim of this study was to describe colorectal tumor profile by age and gender in Gastroentero-Hepatology Center, Dr Soetomo Hospital. This study has received a certificate of Ethical Clearance No.273/Panke.KKE/IV/2015, a descriptive retrospective study. We collected data using medical records, and patients who have been colonoscopy examination and suspected colorectal tumor were included. There were 201 patients, divided to 100 males and 101 females. The peak of incidence was on 51-60 years old group, but on the 31-40 years old incidence of colorectal tumor was increased. The youngest patient was 17 years old. And tumors are more likely develop in distal area, especially in rectum. This study shows a different characteristic profile of colorectal tumor, where tumor is developed at young people and there is no significant difference between male and female for the incidence.